Pengembangan Media Fish Pond Market untuk Stimulasi Pemahaman Numerasi Rupiah Anak Usia 5-6 Tahun - Putri Nada Aprilia; Gilar Gandana; Budi Iskandar (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Understanding rupiah numeracy is an essential skill that should be developed from an early age because it supports children's ability to recognize, compare, and use money in everyday life. However, existing learning media have not provided concrete and contextual learning experiences that suit the characteristics of young children. This study aimed to develop the Fish Pond Market learning media and examine its feasibility and effectiveness in stimulating rupiah numeracy understanding among children aged 5–6 years. The study employed the Design-Based Research (DBR) approach based on the Amiel and Reeves model, consisting of problem identification, solution development, media testing and refinement, and reflection. The research was conducted at RA Al-Barokah and involved 21 children in Group B. Data were collected through interviews, expert validation, and observations, then analyzed using descriptive quantitative and qualitative methods. The results showed that the Fish Pond Market media achieved a feasibility score of 97.62% from the media expert and 100% from both the material expert and practitioner, indicating that it was suitable for classroom implementation. The trial also demonstrated its effectiveness in stimulating children's rupiah numeracy understanding, as the number of children categorized as Very Well Developed (BSB) increased from 7 to 19 after using the media. Therefore, the Fish Pond Market media is recommended as an alternative learning medium for stimulating rupiah numeracy understanding among children aged 5–6 years